Algebraic Expressions
Factoring and expanding algebraic expressions, rules for transforming algebraic expressions
Factoring algebraic expressions - methods, the greatest common factor
Factoring by grouping
Perfect square trinomials - the square of a binomial
The difference of two squares
The sum and difference of cubes
Using a variety of methods including combinations of the above to factorize algebraic expressions
Factoring algebraic expressions
Factoring algebraic expression by finding (determining) the greatest common factor
 Examples: a)  3x - 6y = 3 · (x - 2y),     b)  xy - y2  = y · (x - y),     c)  a - a2  = a · (1 - a), d)  x3 -3x2  + x = x · (x2 - 3x +1),    e)  x(a + b) - (a + b) = (a + b) · (x - 1), f)   a(x - 3y) - x + 3y  = a(x - 3y) - (x - 3y) = (x - 3y) · (a - 1).
Grouping like terms, grouping and factorizing four terms
An addition sign, or plus sign, in front of the brackets leaves the sign of every term inside the brackets unchanged.
A minus sign in front of the bracket indicates that, when removing the bracket, the sign of all terms inside must be changed.
 Examples: a)  ax - bx - a + b = x(a - b) - (a - b) = (a - b) · (x - 1), b)  a - 1 - ab + b = (a - 1) - b · (a - 1) = (a - 1) · (1 - b), c)  x2 + ax - bx - ab = x(x + a) - b · (x + a) = (x + a) · (x - b), d)  5ab2 - 3a3 - 10b3 + 6a2b = 5b2(a - 2b) -3a2(a - 2b) = (a - 2b)(5b2 - 3a2).
Perfect square trinomials - the square of a binomial
 Examples: a)  1 - 4x + 4x2 = 12  - 2 · 2x + (2x)2 = (1 - 2x)2  = (1 - 2x) · (1 - 2x), b)  a5 + 6a4b + 9a3b2 = a3 · (a2  + 6ab  + 9b2 ) = a3(a + 3b)2 = a3(a + 3b)(a + 3b).
The difference of two squares
 Examples: a)  16x2 - 1 = (4x)2 - 12 = (4x -1) · (4x +1), b)  5y3 - 20x2y = 5y · (y2 - 4x2) = 5y [y2  - (2x)2] = 5y(y - 2x)(y + 2x), c)   9x2  - (x + 2)2 = [3x - (x + 2)] · [3x + (x + 2)] = (2x -2) · (4x + 2) = 4(x -1) · (2x +1).